Methodological issues in socio-economic development - Ahmed, Ansar; Chandrasekar, Ruben (Concept Publishing Company, 2017)
This book chapter was published in the City Society and Planning : Essays in Honour of Professor A K Dutt (3 Vols-Set) [© 2007 Concept Publishing Company] and the content page is available at: http://www.vedamsbooks.com/product_detail_print.htm?pid=27800